Načini oblikovanja popularnoglasbenih priredb ljudskih pesmi - Šivic, Urša (Traditiones (Ljubljana), 2006)
Like art music, popular music has always had at least some connections with folk music. The paper looks at the ways in wich Slovenian folk music has benn used and transformd in popular songs that contain elements of folk music, and examined both types of music that are sociologically, poetologically, and structurally very different.
Keywords: ethnology; etnologija; folk music; ljudska glasba; popularna glasba; slovenske ljudske pesmi; priredbe; muzikologija